2013
DOI: 10.1177/1753193413484629
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of radiographic classification of scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC) wrist

Abstract: The aim of this study was to measure inter- and intra-observer agreement on the radiographic classification of scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC) wrist. Radiographs of 41 patients with SLAC wrist and 47 patients with SNAC wrist were graded on two separate occasions by four orthopaedic consultants specializing in hand and wrist surgery. Inter-observer agreement was evaluated using the multi-rater kappa value. Landis and Koch criteria were used to assess the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…One study showed moderate interobserver and substantial intraobserver reliability for SLAC, with kappa of 0.59 and 0.65, respectively. 17 For SNAC measures of reliability were lower with slight interobserver and fair moderate interobserver agreement (kappa: 0.20 and 0.29, respectively). 17 Another study demonstrated low interobserver agreement with kappa < 0.5 among five different readers, with the level of agreement being unrelated to the level of expertise of the reader.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One study showed moderate interobserver and substantial intraobserver reliability for SLAC, with kappa of 0.59 and 0.65, respectively. 17 For SNAC measures of reliability were lower with slight interobserver and fair moderate interobserver agreement (kappa: 0.20 and 0.29, respectively). 17 Another study demonstrated low interobserver agreement with kappa < 0.5 among five different readers, with the level of agreement being unrelated to the level of expertise of the reader.…”
Section: Discussionmentioning
confidence: 91%
“…17 For SNAC measures of reliability were lower with slight interobserver and fair moderate interobserver agreement (kappa: 0.20 and 0.29, respectively). 17 Another study demonstrated low interobserver agreement with kappa < 0.5 among five different readers, with the level of agreement being unrelated to the level of expertise of the reader. 18 The authors suggested that a more reliable method than radiographic staging is required to assess OA in these patients when planning treatment.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] With scaphoid nonunion, the wrist can frequently become pa inful with loss of function and progressive degenerative changes or carpal arthritis. To diminish symptoms and arthrosis over the long term, it has been emphasized that surgery for scaphoid nonunions should achieve a bony union and restore normal anatomy of the scaphoid and carpal mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies 13,20 concluded that SNAC staging based on anteroposterior (AP) radiographs has limited reliability. One possibility is that it can be difficult to distinguish between early stages of osteoarthritis and normal anatomy.…”
Section: Introductionmentioning
confidence: 99%